2007
DOI: 10.1017/s0022112007006921
|View full text |Cite
|
Sign up to set email alerts
|

Rough-wall boundary layers: mean flow universality

Abstract: Mean flow profiles, skin friction, and integral parameters for boundary layers developing naturally over a wide variety of fully aerodynamically rough surfaces are presented and discussed. The momentum thickness Reynolds number Re θ extends to values in excess of 47 000 and, unlike previous work, a very wide range of the ratio of roughness element height to boundary-layer depth is covered (0.03 < h/δ < 0.5). Comparisons are made with some classical formulations based on the assumption of a universal twoparamet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
134
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 169 publications
(148 citation statements)
references
References 24 publications
(41 reference statements)
13
134
0
1
Order By: Relevance
“…In particular, figure 6(a) shows results for the indirect method (via equation 2.1) and figure 6(b) using the direct method (friction-balance) for skin-friction estimation. This type of plot was first proposed by Castro (2007) and will allow us to estimate if the current data agrees with previous findings. Most of the results from rough-wall studies have been found to scatter around the two curves (for different values of wake parameter Π) shown in figure 6 (Castro 2007).…”
Section: Effect Of Surface Morphology On Aerodynamic Parameterssupporting
confidence: 61%
See 4 more Smart Citations
“…In particular, figure 6(a) shows results for the indirect method (via equation 2.1) and figure 6(b) using the direct method (friction-balance) for skin-friction estimation. This type of plot was first proposed by Castro (2007) and will allow us to estimate if the current data agrees with previous findings. Most of the results from rough-wall studies have been found to scatter around the two curves (for different values of wake parameter Π) shown in figure 6 (Castro 2007).…”
Section: Effect Of Surface Morphology On Aerodynamic Parameterssupporting
confidence: 61%
“…where the Reynolds shear stress is evaluated from the plateau region in the roughness sublayer (as in Flack et al 2005 andCastro 2007). Both these above-mentioned approaches yield a U τ value that is within 5% of each other.…”
Section: Indirect Estimate Of Skin-frictionmentioning
confidence: 99%
See 3 more Smart Citations